2018
DOI: 10.1007/s10597-018-0320-2
|View full text |Cite
|
Sign up to set email alerts
|

From Physical Wellness to Cultural Brokering: Unpacking the Roles of Peer Providers in Integrated Health Care Settings

Abstract: This qualitative study explored peer provider experiences working in newly integrated mental health and primary care pilot programs within a large public mental health system. Nineteen peer providers participated in semistructured interviews that focused on experiences delivering care within integrated teams. Interviews were analyzed using constant comparative methods informed by grounded theory. Findings were organized into three themes that speak to variation in the definition and function of peers; lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…An organizational culture that leads services to adopt a risk-averse approach (Ibrahim et al, 2020 ) is suggested as a potential barrier to introducing peer workers’ roles. Earlier studies have pointed to the need to clarify peer workers' roles (Burke et al, 2018 ; Gidugu et al, 2015 ; Siantz et al, 2018a ), and it has been suggested that organizations give peer workers conventional roles rather than creating roles focusing on their positions and qualifications to minimize the presence or effects of risk (Bellamy et al, 2017 ; Byrne et al, 2021b ; Ibrahim et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An organizational culture that leads services to adopt a risk-averse approach (Ibrahim et al, 2020 ) is suggested as a potential barrier to introducing peer workers’ roles. Earlier studies have pointed to the need to clarify peer workers' roles (Burke et al, 2018 ; Gidugu et al, 2015 ; Siantz et al, 2018a ), and it has been suggested that organizations give peer workers conventional roles rather than creating roles focusing on their positions and qualifications to minimize the presence or effects of risk (Bellamy et al, 2017 ; Byrne et al, 2021b ; Ibrahim et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, peer workers as providers of peer support were often told to be service users’ advocates, increasing their involvement with the services, as well as bridging and helping service users navigate the service systems. This position seems to be linked to two crucial factors: peer workers easily connect with service users because of their similar backgrounds (Ranzenhofer et al, 2020 ; Roennfeldt & Byrne, 2020 ; Van Zanden & Bliokas, 2021 ; Weir et al, 2019 ; Zeng & Chung, 2019 ), and peer workers are employed within the services, so they are familiar with the organizations and the organizational language (Kidd et al, 2016 ; Lennox et al, 2021 ; Mutschler et al, 2019 ; Siantz et al, 2018a ; Storm et al, 2020 ). In short, peer workers have knowledge of the rules of interactions in both worlds (MacLellan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Despite the increase in peer-led services within behavioral health care, gaps in research on the peer workforce remain. Presently, no standardized language defining peer provider scope of practice and service delivery roles exists across state legislations, 13,14 and there are no uniform peer certification and training standards. This review provides an indepth assessment of current literature on the roles and efficacy of peer providers in the behavioral health workforce.…”
Section: Contextmentioning
confidence: 99%
“…The majority (11 studies) reported data collection having occurred at 3 timepoints, 17,19,20,22,23,29,31,32,34,37,38 with measurements most commonly occurring at baseline, at 3 months, and at 6 months after intervention. A total of 21 studies provided sources for covariate data, with the most frequently referenced data sources being self-reported information provided at study baseline (14 studies), [17][18][19][20][21][22][23][24]26,28,[31][32][33]38 medical records (10 studies), 19,22,25,28,[30][31][32][33][34]39 and county-derived or regional network demographic and service use data (3 studies). 23,27,35 A total of 8 studies reported conducting an intent-to-treat analysis, 17,19,23,25,26,31,36,37 and 3 studies utilized both intent-to-treat ...…”
Section: (Available Online)mentioning
confidence: 99%
“…Formally, employed service-users occupy a unique position by leveraging their lived experiences of using services to become integrated within an organization and then co-produce that same service. As such, formally employed service-users can occupy a brokering role (Siantz et al, 2018). They are theoretically able to translate differing professional and user perspectives, based on their own experiences, developing the collaborative relationships necessary to mediate professional dominance in processes of co-production.…”
Section: Introductionmentioning
confidence: 99%